Efektivitas Penerapan Model Project Based Learning (PjBL) Terhadap Keterampilan Berbicara (Speaking) Siswa Pada Mata Pelajaran Bahasa Inggris Kelas VIII MTs Muhammadiyah Kota Solok - Afifah, Fathimah Afifatuzzahra; Reni Kurnia; Rahmi Pratiwi; Rosmaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low speaking skills of eighth-grade students in English learning at MTs Muhammadiyah Kota Solok. The identified problems include limited vocabulary, errors in pronunciation and grammatical structure, and the lack of opportunities for students to practice speaking due to teacher-centered learning. These conditions have an impact on students' learning outcomes, especially in the asking and giving opinion material, which requires active oral communication skills.This study aims to determine the effectiveness of the Project Based Learning (PjBL) model in improving students' speaking skills. The research method used was a quantitative approach with a pre-experimental design, namely a one-group pretest-posttest design. The subjects of this study consisted of 21 students. Data were collected through speaking tests covering aspects of fluency, pronunciation, grammar, and vocabulary. The data were analyzed using descriptive statistics and paired sample t-test after fulfilling the prerequisite tests, namely normality and homogeneity tests.The results showed an improvement in students’ speaking skills after the implementation of Project Based Learning. The mean score of the pretest was 44.29, which increased to 75.60 in the posttest. The hypothesis testing showed a significance value of 0.000 < 0.05, indicating a significant difference between before and after the treatment. In conclusion, Project Based Learning is effective in improving students’ speaking skills in English learning, particularly in the asking and giving opinion material.